Stratifying stroke severity: towards a personalised medicine application for primary care - Akyea, Ralph Kwame (2022)
Stroke remains a major cause of death and disability worldwide, despite advances in prevention and treatment. Improvements in acute care have led to many surviving after an incident stroke event. However, the prognosis after surviving remains compromised. This is due to the high risk of recurrent adverse cardiovascular events, greatest during the first year but persisting over one’s lifetime. Reducing long-term residual cardiovascular risk and improving quality of life are primary goals for clinical practice and research. Identifying patients at the greatest risk of subsequent major adverse cardiovascular events (MACE) could help clinicians and policymakers determine which patients need to be prioritised.